2019
DOI: 10.1128/mbio.00292-19
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Vibrio FliL, a New Stomatin-like Protein That Assists the Bacterial Flagellar Motor Function

Abstract: Many motile bacteria swim or swarm using a filamentous rotating organelle, the flagellum. FliL, a component protein of the flagellar motor, is known to enhance the motor performance under high-load conditions in some bacteria. Here we determined the structure of the periplasmic region of FliL (FliLPeri) of the polar flagellum of Vibrio alginolyticus. FliLPeri shows a remarkable structural similarity to the stomatin/prohibitin/flotillin/HflK/C (SPFH) domain of stomatin family proteins, some of which are involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…Flagella assembly is controlled by FleQ, an NtrC‐like transcriptional regulator which controls synthesis of flagellar genes and its expression, in other flagellated bacteria, was shown to be cold‐induced, based on an 83% decrease in fleQ transcripts at 30°C compared with 4°C (Soutourina et al ., ). The flagellar protein, FliL, which is a single‐transmembrane protein with a large periplasmic region and associates with the flagellar basal body, has been found to be important for the function of the motor under high‐load conditions, such as highly viscous environments, by recruiting or stabilizing the stators or by increasing their efficiency, leading to greater torque generation (Partridge et al ., ; Takekawa et al ., ). Flagellin is the major structural protein of the flagella filaments, which in O .…”
Section: Discussionmentioning
confidence: 97%
“…Flagella assembly is controlled by FleQ, an NtrC‐like transcriptional regulator which controls synthesis of flagellar genes and its expression, in other flagellated bacteria, was shown to be cold‐induced, based on an 83% decrease in fleQ transcripts at 30°C compared with 4°C (Soutourina et al ., ). The flagellar protein, FliL, which is a single‐transmembrane protein with a large periplasmic region and associates with the flagellar basal body, has been found to be important for the function of the motor under high‐load conditions, such as highly viscous environments, by recruiting or stabilizing the stators or by increasing their efficiency, leading to greater torque generation (Partridge et al ., ; Takekawa et al ., ). Flagellin is the major structural protein of the flagella filaments, which in O .…”
Section: Discussionmentioning
confidence: 97%
“…The motor of this spirochete also possesses a particular structure, called the collar, to which FliL is associated (18). Furthermore, biochemical and X-ray crystallography studies in V. alginolyticus suggested that rings of FliL might associate around stator units (19,20). From these and other studies, it may be concluded that FliL is a small membrane protein that is part of the flagellar basal body and that might have a role in stabilizing the stator (21).…”
mentioning
confidence: 90%
“…In addition to the paucity of studies on the role of FliL in alphaproteobacteria, there are no comparative works in bacterial species possessing two flagellar systems except for recent studies in V. alginolyticus (19,20). Since B. diazoefficiens uses its two flagellar systems for swimming (2), this species brings an opportunity to compare the role of FliL in each system for swimming.…”
mentioning
confidence: 99%
“…Besides, in Vibrio the proteins MotY and MotX form the periplasmic T-ring that interacts with PomB (equivalent to MotB in Vibrio) and stabilize the stator complexes [25,26]. Activation of the proton channel requires extensive remodeling of the periplasmic region of MotB [27][28][29][30][31][32], and it has been proposed that the flagellar protein FliL participates in this process [33][34][35][36][37].…”
Section: The Flagellar Structurementioning
confidence: 99%